(untitled)
We document that home ownership of households with heads aged 25-44 years fell substantially between 1980 and 2000 and recovered only partially during the 20012005 housing boom. The 19802000 decline in young home ownership occurred as improvements in mortgage opportunities made it easier to purchase a home. This paper uses an equilibrium life-cycle model calibrated to micro and macro evidence to understand why young home ownership fell over a period when it became easier to own a home. Our findings indicate that a trend toward marrying later and the increase in household earnings risk that occurred after 1980 account for 3/5 to 4/5 of the decline in young home ownership., address = London, author = Jonas D. M. Fisher and Martin Gervais, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = E0; E2; J1; R21; 330; Housing; home ownership; tenure choice; first-time home-buyers; marriage; income risk; Grundbesitz; Wohneigentum; Altersgruppe; Ehe; Arbeitsmarkt; Risiko; Lebenszyklus; Großbritannien, language = eng, number = 09,08, publisher = Institute for Fiscal Studies (IFS), title = Housing, home ownership, tenure choice, first-time home-buyers, marriage, income risk, type = IFS Working Papers, url = https://hdl.handle.net/10419/47481, year = 2009